UPAYA MENINGKATKAN KINERJA MELALUI OPTIMALISASI DISIPLIN KERJA - Catur Galuh Ratnagung (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
Lack of teacher discipline has an impact on student achievement. However, the real bad side is moral degradation. Therefore it is important to maintain teachers, one of them is work discipline. The purpose of this study was to determine the effect of work discipline on performance. The research method used is quantitative descriptive. The sample technique used is the Accidental Sampling technique, which amounted to 56 respondents. The analytical method used is linear regression consisting of validity test, reliability test, correlation coefficient test, coefficient of determination test, simple regression test, and hypothesis test. The results showed that work discipline had a significant effect on performance. The meaning of influence is that all disciplinary instruments have the potential to control the manner and work behavior of the teacher